2011
DOI: 10.1002/cphc.201100515
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence Quenching of CdS Quantum Dots by 4‐Azetidinyl‐7‐Nitrobenz‐2‐Oxa‐1,3‐Diazole: A Mechanistic Study

Abstract: Fluorescence quenching of CdS quantum dots (QDs) by 4-azetidinyl-7-nitrobenz-2-oxa-1,3-diazole (NBD), where the two quenching partners satisfy the spectral overlap criterion necessary for Förster resonance energy transfer (FRET), is studied by steady-state and time-resolved fluorescence techniques. The fluorescence quenching of the QDs is accompanied by an enhancement of the acceptor fluorescence and a reduction of the average fluorescence lifetime of the donor. Even though these observations are suggestive of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
33
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 58 publications
8
33
0
Order By: Relevance
“…In one of our earlier works, while we highlighted this important point using one specific example, we could not provide evidence of the alternate mechanism due to lack of ultrafast pump-probe facility at that time. 40 In this work, we study the interaction between water soluble mercaptopropanoic acid capped photoexcited CdTe QDs and CV, a pair chosen for satisfying excellent overlap of the emission spectrum of former with the absorption spectrum of the latter. We not only show that despite fulfilling the overlap criteria, the emission quenching of the QDs is not governed by FRET interaction of the two species, but employing femtosecond time-resolved transient absorption measurements we demonstrate that ultrafast photo-induced electron transfer from the conduction band of the QDs to CV is primarily response for the exciton quenching process.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In one of our earlier works, while we highlighted this important point using one specific example, we could not provide evidence of the alternate mechanism due to lack of ultrafast pump-probe facility at that time. 40 In this work, we study the interaction between water soluble mercaptopropanoic acid capped photoexcited CdTe QDs and CV, a pair chosen for satisfying excellent overlap of the emission spectrum of former with the absorption spectrum of the latter. We not only show that despite fulfilling the overlap criteria, the emission quenching of the QDs is not governed by FRET interaction of the two species, but employing femtosecond time-resolved transient absorption measurements we demonstrate that ultrafast photo-induced electron transfer from the conduction band of the QDs to CV is primarily response for the exciton quenching process.…”
Section: Introductionmentioning
confidence: 99%
“…Difference absorption spectra of the QDs (7 μM) in aqueous medium in the absence (a) and presence (b) of CV (7 μM) at various delay times(2,5,10,20,30,40,60, 70, 100 ps) after 350 nm excitation.…”
mentioning
confidence: 99%
“…Surface ligands depessivation can be one of the reasons for fluorescence quenching of nanocrystals . Due to depassivation of surface ligands by external influences, destruction of electron‐hole recombination state (exciton) takes place leading to quenching of fluorescence.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, Santhosh et al . have shown that spectral overlap is not the sole criteria for resonance energy transfer between azetidinyl‐NBD and CdS quantum dots as in‐depth analysis over this system indicated the presence of static quenching and charge transfer between the dyad.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation